Exposed and concealed antigens as vaccine targets for controlling ticks and tick-borne diseases. - Nuttall, P; Trimnell, A; Kazimirova, M; Labuda, M (2006)
Tick vaccines derived from Bm86, a midgut membrane-bound protein of the cattle tick, Boophilus microplus, are currently the only commercially available ectoparasite vaccines. Despite its introduction to the market in 1994, and the recognized need for alternatives to chemical pesticides, progress in developing effective antitick vaccines (and ectoparasite vaccines in general) is slow. The primary rate-limiting step is the identification of suitable antigenic targets for vaccine development. Two sources of candidate vaccine antigens have been identified: 'exposed' antigens that are secreted in tick saliva during attachment and feeding on a host and 'concealed' antigens that are normally hidden from the host. Recently, a third group of antigens has been distinguished that combines the properties of both exposed and concealed antigens. This latter group offers the prospect of a broad-spectrum vaccine effective against both adults and immature stages of a wide variety of tick species. It also shows transmission-blocking and protective activity against a tick-borne pathogen. With the proliferation of molecular techniques and their application to vaccine development, there are high hopes for new and effective antitick vaccines that also control tick-borne diseases.